The Effect of Company Size and Good Corporate Governance on Company Value (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to determine and analyze the effect of company size and Good Corporate Governance (Institutional Ownership, Independent Board of Commissioners, and Audit Committee) on Company Value in energy sector issuers listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The research method applied in this study is a quantitative approach using secondary data obtained from company annual reports. The population includes energy companies operating in the Oil, Gas, and Coal sub-sectors. The sample was determined through purposive sampling, resulting in 60 data observations consisting of 15 companies over four consecutive years. The analytical technique employed utilizes SPSS software version 55 with multiple linear regression analysis to examine the relationships among variables. The results indicate that company size significantly influences company value. Good corporate governance proxied by institutional ownership shows a negative effect on firm value, while independent commissioners and audit committees have no significant effect. Simultaneous findings confirm that company size and good corporate governance together influence firm value.